HUBUNGAN ANTARA PENGETAHUAN DAN SIKAP PASIEN INFEKSI MENULAR SEKSUAL (IMS) DENGAN PERILAKU PENCEGAHAN PENULARAN IMS DI WILAYAH KERJA PUSKESMAS KOM YOS SUDARSO PONTIANAK - ., Siti Fatimah (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2013)
Background: Sexually Transmitted Infections (STIs) and its complicationsin developing countries was being the top five categories of adult diseasesthat require great quantities of health care. Sexually transmitted infectionscan cause acute symptoms, chronic infections and serious consequencessuch as infertility, ectopic pregnancy, cervical cancer and sudden death ininfants and adults. Objective: The purpose of this research was todetermine the relation between the knowledge and attitude of SexuallyTransmitted Infections (STIs) patient towards the level of the preventiontransmission of Sexually transmitted infections behavior in Kom YosSudarso Clinic Pontianak City. Method: This research was an analyticobservational study with cross sectional approach. It was conducted atKom Yos Sudarso Clinic, Pontianak City, on April-Juli 2013. Data wereobtained from 50 Sexually transmitted infections(STIs) patient and wereanalyzed through comparative analysis using Chi-Square test. Result:The result shows that 58% of respondents have good level of theprevention transmission of STIs behavior. There is a significant relationbetween the knowledge towards the level of the prevention transmission ofSTIs behavior (p=0,000) and there is a significant relation between theattitude towards the level of the prevention transmission of STIs behavior(p=0,000). Conclusion: There are significant relation between knowledgetowards the level of the prevention transmission of STIs behavior and theattitude towards the level of the prevention transmission of STIs behavior.The level of the prevention transmission of STIs behavior will increase ifthe knowledge and attitude improve.Keyword: knowledge, attitude, level of the prevention transmission ofSexually Transmitted Infections(STIs) behavior